2014
DOI: 10.1016/b978-0-12-411638-2.00004-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Genetic Imaging of Cancer

Abstract: Molecular-genetic imaging of cancer using nonviral delivery systems has great potential for clinical application as a safe, efficient, noninvasive tool for visualization of various cellular processes including detection of cancer, and its attendant metastases. In recent years, significant effort has been expended in overcoming technical hurdles to enable clinical adoption of molecular-genetic imaging. This chapter will provide an introduction to the components of molecular-genetic imaging and recent advances o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 155 publications
0
23
0
Order By: Relevance
“…A transcription-based imaging, therapeutic or theranostic system can be considered for clinical translation if it meets certain criteria such as high tumor specificity, broad application and minimal toxicity (1, 2). The first two criteria can be met through the choice of a strong and tumor-specific promoter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A transcription-based imaging, therapeutic or theranostic system can be considered for clinical translation if it meets certain criteria such as high tumor specificity, broad application and minimal toxicity (1, 2). The first two criteria can be met through the choice of a strong and tumor-specific promoter.…”
Section: Introductionmentioning
confidence: 99%
“…The first two criteria can be met through the choice of a strong and tumor-specific promoter. For example, cancer-specific gene therapy with the osteocalcin promoter, delivered through intra-lesional administration of an adenoviral vector, caused apoptosis in a subset of patients with prostate cancer (PCa) (2, 3). We have shown that cancer-specific imaging could be accomplished in experimental models of human melanoma and breast cancer by systemic delivery of imaging reporters under the transcriptional control of the progression elevated gene-3 promoter (PEG-Prom) (1, 4).…”
Section: Introductionmentioning
confidence: 99%
“…While this mimics the variation observed in human cancers, it makes particular therapeutic approaches more challenging, such as early detection, cancer vaccine development, and preventative therapies. To address this problem, bioluminescent markers have been utilized to enable tumor monitoring through noninvasive imaging (Minn et al, 2014;Pomper & Fisher, 2014). Moreover, metastases can be identified through these imaging techniques, opening the door to more thoroughly test antimetastatic therapies (Minn et al, 2014;Pomper & Fisher, 2014).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Bioluminescence imaging (BLI) is a noninvasive, quantitative method of detecting metastases in mice in vivo (Badr, 2014; Contag et al, 1995; Minn et al, 2014). It is generally the first approach to image gene-tagged cells in vivo, when populations of cells rather than single cells are to be studied.…”
Section: Approaches Currently Used To Detect Metastatic Lesions (Omentioning
confidence: 99%
“…Molecular-genetic imaging approaches allow visualizing and quantifying biochemical processes at the cellular and molecular level (Bhang & Pomper, 2012; Minn et al, 2014; Pomper & Fisher, 2014). The basic components for molecular-genetic imaging are gene promoters, reporters, and gene delivery vehicles.…”
Section: Approaches Currently Used To Detect Metastatic Lesions (Omentioning
confidence: 99%